A prospective study on maternal periodontal diseases and neonatal adverse outcomes - Ping Wen; Huijun Li; Xiaoyi Xu; Feng Zhang; Dan Zhao; Rong Yu; Tianfan Cheng; Hao Wang; Chuanzhong Yang; Wei Qin; Xiuqiao Yang; Jilong Yao; et al. (Medical Journals Sweden, 2024)
Objective: It is evident that periodontitis is linked to various adverse pregnancy outcomes. This prospective study explored the potential link of maternal periodontal diseases to neonatal adverse outcomes. Materials and Methods: A total of 193 generally healthy females in their third trimester (34-36 weeks) of pregnancy were enrolled. All subjects received full-mouth periodontal assessment, and the periodontal inflamed surface area (PISA) was calculated. Demographic data, lifestyles and anthropometric measurements of the neonates (e.g., body length and head circumference) were recorded. Herein, small-for-gestational age (SGA) referred to gender- and age-adjusted birth weight below the 10th percentile in line with the standard reference. Multivariable logistic regression analysis and restricted cubic spline were performed for examining the association of periodontal parameters with SGA.  Results: There were 8.3% (16/193) of neonates with SGA. Significantly positive correlation existed between the percentage of tooth sites with increased probing depth and an elevated risk of SGA (OR: 1.052; P < 0.05). Yet, the PISA was positively associated with the risk of SGA (OR: 1.002; P < 0.05) as well. No significant link occurred between maternal periodontal status and other neonatal outcome measures. Conclusion: Within the limitations of this study, the findings suggest that there could be a link between maternal periodontal diseases and neonatal adverse outcomes like SGA. Further investigation is required to clarify the current findings and potential implications for promoting maternal oral/periodontal health and newborn health.